2021
DOI: 10.1177/09603271211021880
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of CTRP12 ameliorates hypoxia/re-oxygenation-induced cardiomyocyte injury by inhibiting apoptosis, oxidative stress, and inflammation via the enhancement of Nrf2 signaling

Abstract: C1q/TNF-related protein 12 (CTRP12) has been reported to play a key role in coronary artery disease. However, whether CTRP12 plays a role in the regulation of myocardial ischemia-reperfusion injury is not fully understood. The goals of this work were to assess the possible relationship between CTRP12 and myocardial ischemia-reperfusion injury. Here, we exposed cardiomyocytes to hypoxia/re-oxygenation (H/R) to establish an in vitro cardiomyocyte injury model of myocardial ischemia-reperfusion injury. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…CCK-8 assays and the determination of LDH activity are sensitive tools for evaluating myocardial cell viability and injury, respectively ( 35 ). In the present study, following CTRP12 overexpression, cell viability was significantly improved and LDH activity was significantly reduced, supporting the hypothesis that CTRP12 has a protective effect against I/R-induced cardiomyocyte injury, which is consistent with previous studies ( 17 , 36 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CCK-8 assays and the determination of LDH activity are sensitive tools for evaluating myocardial cell viability and injury, respectively ( 35 ). In the present study, following CTRP12 overexpression, cell viability was significantly improved and LDH activity was significantly reduced, supporting the hypothesis that CTRP12 has a protective effect against I/R-induced cardiomyocyte injury, which is consistent with previous studies ( 17 , 36 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Fadaei et al ( 16 ) reported that the serum levels of CTRP12 were decreased and negatively associated with TNF-α and IL-6 in patients with coronary artery disease. Consistent with previously published findings ( 36 ), the results of the present study demonstrated that the secretory levels of TNF-α, IL-1β and IL-6 were significantly increased in cell culture supernatants from H/R-treated cells, whereas CTRP12 overexpression significantly abrogated this effect. These findings indicated that CTRP12 overexpression may protect cardiomyocytes against H/R-induced inflammation.…”
Section: Discussionsupporting
confidence: 93%